Altered properties of quantal neurotransmitter release at endplates of mice lacking P/Q-type Ca2+ channels - Urbano, FJ; Piedras-Renteria, ES; Jun, KS; Shin, HS; Uchitel, OD; Tsien, RW (NATL ACAD SCIENCES, 2003)
Transmission at the mouse neuromuscular junction normally relies on P/Q-type channels, but became jointly dependent on both Nand R-type Ca2+ channels when the P/Q-type channel alpha(1A) subunit was deleted. R-type channels lay close to Ca2+ sensors for exocytosis and I-K(Ca) channel activation, like the P/Q-type channels they replaced. In contrast, N-type channels were less well localized, but abundant enough to influence secretion strongly, particularly when action potentials were prolonged. Our data suggested that active zone structures may select among multiple Ca2+ channels in the hierarchy P/Q>R>N. The alpha(1A)-/- neuromuscular junction displayed several other differences from wild-type: lowered quantal content but greater ability to withstand reductions in the Ca2+/Mg2+ ratio, and little or no paired-pulse facilitation, the latter findings possibly reflecting compensatory mechanisms at individual release sites. Changes in presynaptic function were also associated with a significant reduction in the size of postsynaptic acetylcholine receptor clusters..
Keywords: MEDIATE TRANSMITTER RELEASE; CALCIUM-CHANNELS; SYNAPTIC-TRANSMISSION; NEUROMUSCULAR-JUNCTIONS; MULTIPLE TYPES; P-TYPE; N-TYPE; PRESYNAPTIC LOCALIZATION; POTASSIUM CHANNELS; ALPHA(1B) SUBUNIT